Influence of Al doping on random lasing in ZnO nanorods - Fadzliana, N.; Samsuri, S.A.M.; Chan, S.Y.; Hsu, H.C.; Maryam, W. (Elsevier, 2020)
Random lasing was demonstrated from aluminum doped ZnO nanorods fabricated on ITO coated glass substrates using simple chemical deposition technique. Different Aluminum (Al) doping parameters were explored in an attempt to realize low threshold ZnO random lasers. Results confirm threshold was strongly dependent on doping concentration and suggestive of resonant coupling with Al in lowering the threshold by 2 orders of magnitude when compared to undoped ZnO nanorods. Lowest threshold was obtained from ZnO nanorods doped with 10 mM of aluminum, suggesting best doping concentration for ZnO random lasers formed by nanorod array. Results further indicate possibility of controlling random lasing properties by adjusting the doping concentration.